198 Digital information for patients requiring inter-hospital transfers: benefits of co-production. Issue 6 (27th May 2022) - Wu, Kit; King, Rachel; Ellis, Cathy; Larcombe, Karen; Dilley, Michael
Abstract : Introduction: Patients admitted with neurological conditions often require transfer to a regional neuroscience centre for further investigations and management. For healthcare teams, inter-hos- pital transfer (IHT) is a complex process to coordinate. For patients and their families, it is a daunting experience with uncertain outcomes [Bosk et al, 2011]. Yet, there is no available digital information on the process of IHT for patients on the internet. Aim: To produce publicly available digital patient information [leaflet] on the process of IHT in collaboration with patients. Method and Results : We collaborated with patient representatives from key stakeholder organisa- tions and charities [South London Neuroscience Operational Delivery Network (ODN), King's Health Partners (KHP), Neurological Alliance and the Brain and Spine Foundation] through co-production meetings set up jointly by ODN and KHP. Together, we defined the target service users and an outline of the content. Building on the digital capabilities of the charities, we defined the host site, its sustainability and maintenance. Thirdly, we defined how healthcare networks will facilitate the dissemination of information in reciprocity. Conclusion: To our knowledge, this is the first co-produced information leaflet for neurological patients on IHT available in a digital format. Providing written information is an important part of patient care which can reduce anxiety, manage expectations and improve patient satisfaction. Through collaboration, we, as healthcare organisations, can enable changes that benefit both the patients and the healthcare providers. kitwu@doctors.org.uk